The Impact Of Price And Brand Image On Consumer Loyalties Of Singkong Moro Crips On The Housing Industry In Sari Lampung East Sources Village - Sugiono Sugiono; Hikmatul Aliyah; Rinnanik Rinnanik; Lukmanul Hakim (Utan Kayu Publishing, 2024)
The research aims to find out the impact of packaging, price and brand image on loyalty. Supposed packaging, price and brand image. The study used quantitative research methods, with a total of 97 respondents. Sampling using non-probability sampling techniques with random sample methods. The data analysis techniques used are Data Quality Test, Classical Assumption Test, Double Linear Regression Analysis, Hypothesis Test and Determination Coefficient Test. Based on calculations with some of these techniques and tests, it is known that the packaging individually has no influence on consumer loyalty. While price and brand image have a positive and significant influence on consumer loyalty.